Characterization of the mutagenic spectrum of 4-nitroquinoline 1-oxide (4-NQO) in Aspergillus nidulans by whole genome sequencing - Downes, Damien J.; Chonofsky, Mark; Tan, Kaeling; Pfannenstiel, Brandon T.; Reck-Peterson, Samara L.; Todd, Richard B. (My University, 2014)
4-Nitroquinoline 1-oxide (4-NQO) is a highly carcinogenic chemical that induces mutations in bacteria, fungi, and animals through the formation of bulky purine adducts. 4-NQO has been used as a mutagen for genetic screens and in both the study of DNA damage and DNA repair. In the model eukaryote Aspergillus nidulans, 4-NQO−based genetic screens have been used to study diverse processes, including gene regulation, mitosis, metabolism, organelle transport, and septation. Early work during the 1970s using bacterial and yeast mutation tester strains concluded that 4-NQO was a guanine-specific mutagen. However, these strains were limited in their ability to determine full mutagenic potential, as they could not identify mutations at multiple sites, unlinked suppressor mutations, or G:C to C:G transversions. We have now used a whole genome resequencing approach with mutant strains generated from two independent genetic screens to determine the full mutagenic spectrum of 4-NQO in A. nidulans. Analysis of 3994 mutations from 38 mutant strains reveals that 4-NQO induces substitutions in both guanine and adenine residues, although with a 19-fold preference for guanine. We found no association between mutation load and mutagen dose and observed no sequence bias in the residues flanking the mutated purine base. The mutations were distributed randomly throughout most of the genome. Our data provide new evidence that 4-NQO can potentially target all base pairs. Furthermore, we predict that current practices for 4-NQO−induced mutagenesis are sufficient to reach gene saturation for genetic screens with feasible identification of causative mutations via whole genome resequencing.
Citation: Downes, D., . . . Todd, R. (2014). Characterization of the Mutagenic Spectrum of 4-Nitroquinoline 1-Oxide (4-NQO) in Aspergillus nidulans by Whole Genome Sequencing. G3: Genes, Genomes, Genetics, 4(12), 2483-2492. https://doi.org/10.1534/g3.114.014712
Keywords: Filamentous fungi; Genetic screen; Chemical mutagenesis; 4-nitroquinoline 1-oxide; Whole genome sequencing